2022
DOI: 10.1037/pag0000716
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and visual acuity predict cognitive function in adults aged 45–85 years: Findings from the baseline wave of the Canadian Longitudinal Study on Aging (CLSA).

Abstract: Associations between sensory status and cognitive performance are now widely reported. However, important open questions remain, including whether the associations are similar across sensory modalities, whether sensory status predicts cognitive performance independent of the cognitive task modality, and whether demographic/health variables moderate these associations. We examined data from a population sample of 30,029 Canadians aged 45-85 (the Canadian Longitudinal Study on Aging). Hearing was measured as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 107 publications
0
9
0
Order By: Relevance
“…This structural model remained significant when accounting for sex and did not differ between males and females. Another study by Phillips et al (2022) similarly observed an association between hearing and cognition but no interaction with sex in a national Canadian sample. In contrast, Helzner et al (2005) noted that lower scores on a modified version of the Mini-Mental State Examination (MMSE, Folstein et al 1975) were associated with a higher risk of pure-tone HL, and that this risk was significantly elevated in Black females relative to individuals of other sexes/races.…”
Section: Sex-related Differences In Hearing and Dementiamentioning
confidence: 83%
“…This structural model remained significant when accounting for sex and did not differ between males and females. Another study by Phillips et al (2022) similarly observed an association between hearing and cognition but no interaction with sex in a national Canadian sample. In contrast, Helzner et al (2005) noted that lower scores on a modified version of the Mini-Mental State Examination (MMSE, Folstein et al 1975) were associated with a higher risk of pure-tone HL, and that this risk was significantly elevated in Black females relative to individuals of other sexes/races.…”
Section: Sex-related Differences In Hearing and Dementiamentioning
confidence: 83%
“…The body of evidence on the effects of HA use on cognitive decline is growing, with many cross-sectional and longitudinal studies suggesting that HA use is associated with better cognitive performance ( Deal et al, 2015 ; Castiglione et al, 2016 ; Karawani et al, 2018 ; Sarant et al, 2020 ). However, conflicting outcomes are reported, both in terms of which cognitive functions improve (e.g., significant improvement has been reported for executive function in two studies; Castiglione et al, 2016 ; Sarant et al, 2020 ) but not in a third ( Phillips et al, 2022 ) and in terms of overall outcomes, with several studies finding no association between HA use and improved cognitive performance ( Valentijn et al, 2005 ; van Hooren et al, 2005 ; Lin et al, 2013 ). As mentioned earlier, recent systematic reviews ( Sanders et al, 2021 ; Yang et al, 2022 ; Yeo et al, 2022 ) have disagreed on the effect of HA use on cognition, and the World Health Organization (WHO) currently rates the quality of the current evidence as ‘very low’, with current WHO guidelines for risk reduction of cognitive decline and dementia stating ‘there is insufficient evidence to recommend the use of HAs to reduce the risk of cognitive decline and/or dementia’ ( WHO, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…While these hypotheses provide plausible explanation, further studies are needed to validate the mechanisms linking hearing loss and cognitive decline. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%